1992
DOI: 10.1111/j.1365-2141.1992.tb06444.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin uptake by bone marrow macrophages is independent of the degree of iron saturation

Abstract: The uptake of transferrin by macrophages was studied in relation to the degree of iron saturation. Rat bone marrow derived macrophages were incubated with transferrin labelled with 59Fe and 3H. At 37 degrees C the amount of 59Fe incorporated by macrophages was dependent on the time of incubation. 3H labelled transferrin was found degraded in the supernatants of the cell culture (material not precipitated by trichloroacetic acid) in a time dependent fashion. Taking into account the specific activity of 59Fe-3H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…87 In addition to apolipoproteins (APOA1, APOA2) involved in the plasma transport of lipoproteins, transferrin (TF) and fetuin (AHSG) were also part of this cluster. TF is a plasma protein able to deliver iron to the bone marrow to load newly formed erythrocytes, 88 whereas AHSG is a plasma protein bound to the bone matrix with important functions in regulating bone turnover. 39 The cluster of plasma proteins with coagulation-related functions includes prothrombin (F2), coagulation factors (F9 and F10), fibrinogen alpha and beta chains (FGA and FGB), vitamin K-dependent protein C (PROC), vitamin K-dependent protein S (PROS1), and antithrombin-III (SERPIN C1).…”
Section: Additional Methods Refinementpooling Extractionsmentioning
confidence: 99%
“…87 In addition to apolipoproteins (APOA1, APOA2) involved in the plasma transport of lipoproteins, transferrin (TF) and fetuin (AHSG) were also part of this cluster. TF is a plasma protein able to deliver iron to the bone marrow to load newly formed erythrocytes, 88 whereas AHSG is a plasma protein bound to the bone matrix with important functions in regulating bone turnover. 39 The cluster of plasma proteins with coagulation-related functions includes prothrombin (F2), coagulation factors (F9 and F10), fibrinogen alpha and beta chains (FGA and FGB), vitamin K-dependent protein C (PROC), vitamin K-dependent protein S (PROS1), and antithrombin-III (SERPIN C1).…”
Section: Additional Methods Refinementpooling Extractionsmentioning
confidence: 99%
“…The inconsistency suggests the existence of different mechanisms involved in the endocytic cycles of apo‐Tf and Fe 2 ‐Tf in different types of cells. Rama and Sanchez (1992) investigated the effect of iron saturation on Tf uptake by rat bone‐marrow‐derived macrophages. They found that the uptake of apo‐Tf or Fe 2 ‐Tf by macrophages is identical in relation to time of incubation and the amount of Tf used.…”
Section: Discussionmentioning
confidence: 99%
“…Primary murine macrophages from bone marrow are expanded in vitro either by using L929 supernatants or recombinant macrophages–colony stimulating factor (rM‐CSF) or by thioglycolate elicitation from the peritoneum . This study utilized expansion of macrophages from murine bone marrow using L929 supernatants, as this method has been shown to consistently produce high yields of pure macrophage cultures with properties that are similar to those produced using rM‐CSF, which is more expensive . L929 supernatants were obtained using previously established protocols .…”
Section: Methodsmentioning
confidence: 99%
“…30 This study utilized expansion of macrophages from murine bone marrow using L929 supernatants, as this method has been shown to consistently produce high yields of pure macrophage cultures with properties that are similar to those produced using rM-CSF, which is more expensive. 31,32 L929 supernatants were obtained using previously established ORIGINAL ARTICLE JOURNAL OF BIOMEDICAL MATERIALS RESEARCH A | NOV 2013 VOL 101A, ISSUE 11 protocols. 30 Briefly, L929 cells were cultured in 5 mL RPMI supplemented with 10% FBS, using a T-25 flask.…”
Section: Preparation Of L929 Supernatants To Culture Macrophagesmentioning
confidence: 99%